2010
DOI: 10.1115/1.3106706
|View full text |Cite
|
Sign up to set email alerts
|

Improving Efficiency of a High Work Turbine Using Nonaxisymmetric Endwalls— Part I: Endwall Design and Performance

Abstract: This paper is the first part of a two part paper reporting the improvement of efficiency of a one-and-half stage high work axial flow turbine by nonaxisymmetric endwall contouring. In this first paper the design of the endwall contours is described, and the computational fluid dynamics (CFD) flow predictions are compared with five-hole-probe measurements. The endwalls have been designed using automatic numerical optimization by means of a sequential quadratic programming algorithm, the flow being computed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…Pralsner et al [20] Endwall profiling Total pressure loss coefficient, SKE and TKE (turbulent kinetic energy) Ingram et al [9] Endwall profiling Exit flow angle deviation Germain et al [21] Endwall profiling Combination of total pressure loss coefficient and CSKE Schüpbach et al [22] Endwall profiling CSKE Moon and Koh [2] Streamwise endwall fence Stream wise vorticity no slip condition and are adiabatic. At inlet experimentally measured total pressure profile for 0…”
Section: Numerical Methodologymentioning
confidence: 99%
“…Pralsner et al [20] Endwall profiling Total pressure loss coefficient, SKE and TKE (turbulent kinetic energy) Ingram et al [9] Endwall profiling Exit flow angle deviation Germain et al [21] Endwall profiling Combination of total pressure loss coefficient and CSKE Schüpbach et al [22] Endwall profiling CSKE Moon and Koh [2] Streamwise endwall fence Stream wise vorticity no slip condition and are adiabatic. At inlet experimentally measured total pressure profile for 0…”
Section: Numerical Methodologymentioning
confidence: 99%
“…12,13 Moreover, the concave streamline curvature can raise the local static pressure and reduce the flow velocity. 17 Ingram conducted similar studies and found that the nonaxisymmetric endwall can increase the efficiency of the high-pressure stage of an aircraft turbine by 0.4%. 14,15 Several achievements have been reported.…”
Section: Introductionmentioning
confidence: 95%
“…Germain et al found that the nonaxisymmetric endwall can increase the stage efficiency by 1%. 17 Ingram conducted similar studies and found that the nonaxisymmetric endwall can increase the efficiency of the high-pressure stage of an aircraft turbine by 0.4%. 20 Li et al reviewed the existing nonaxisymmetric endwall technology and proposed a new endwall modelling method.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations